A new species of Coahomasuchus (Archosauria, Aetosauria) from the Upper Triassic Pekin Formation, Deep River Basin, North Carolina. (21st December 2016) - Heckert, Andrew B.; Fraser, Nicholas C.; Schneider, Vincent P.
Abstract: We describe a new species of the aetosaur Coahomasuchus, C . chathamensis, based on an incomplete, but largely articulated, anterior portion of a skeleton recovered from a quarry in the Upper Triassic Pekin Formation of Chatham County, North Carolina. This is only the second documented occurrence of Coahomasuchus, with the other being the holotype of C . kahleorum Heckert and Lucas, 1999 from the Upper Triassic Colorado City Formation of Texas. Although much of the specimen is the same size as the holotype of C . kahleorum, the dorsal paramedian osteoderms of the North Carolina taxon are considerably (~1.3×) wider than homologous counterparts in C . kahleorum, and the ventral thoracic osteoderms are also rectangular (~1.5× wider than long), rather than square, presumably to accommodate the wider body. This is a rare instance where two articulated specimens of closely related aetosaur species are available for direct comparison of homologous osteoderms. Isolated osteoderms with similar ornamentation from the same locality indicate that C . chathamensis may have been one of the earliest aetosaurs to attain the broad osteoderm proportions (width:length >3.5:1) otherwise known solely from later branching, spinose taxa such as Typothorax . The co-occurrence of Lucasuchus and Coahomasuchus in both North Carolina and Texas supports past correlations indicating an Otischalkian (Carnian) age for these strata and demonstrates that plesiomorphic, non-spinose aetosaur genera were not necessarily endemic to a single basin in North America.